System-level finite element analysis of piezoelectric energy harvesters with rectified interface circuits and experimental validation. (April 2021) - Qian, Feng; Liao, Yabin; Zuo, Lei; Jones, Phil
Highlights: Approximates rectified energy harvesting circuits with an equivalent linear circuit. Derives and experimentally validates results for standard AC-DC energy harvesting circuit. Enables system-level finite-element analysis of rectified energy harvesting systems. Investigates the energy harvesting performance of a triangle-shaped beam harvester. Abstract: The finite element method (FEM) has been widely used for numerical studies of piezoelectric energy harvesting (PEH) systems, through commercial finite element (FE) packages or specially developed FE formulations. As a convenient computational tool, FEM can deal with systems of high complexity and has evolved into a multiphasic solution to coupled problems in engineering. However, most of FE packages and formulations are limited to coupled-field simulations of PEH systems connected with a linear circuit. On the other hand, rectified circuits are a critical component in practical applications because electronic devices such as wireless sensor nodes and wearable electronics require a DC power supply. Based on the equivalent impedance analysis, this paper proposes a method to enable a coupled-field study of piezoelectric energy harvesters with the standard AC-DC interface circuit through an equivalent linear circuit. The proposed method enables FE packages and formulations to analyze, design, and optimize PEH harvesters at the system level, by either adding the capability of simulating rectified circuits, or reducing a nonlinear circuit interface simulation into a faster and more stable linear simulation that can be solved more conveniently. This equivalent linear circuit method was applied to a rectangular shaped bimorph beam harvester in ANSYS and validated experimentally. The results also match well with those obtained from a system-level analytical approach. As an application example, a comparison study was performed between the rectangular and triangular energy harvesters using FE packages and the proposed equivalent circuit, given the same natural frequency and material volume. In addition, the implementation of this method with FE formulations is briefly outlined and discussed.